2017
DOI: 10.1161/circinterventions.116.005233
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Fractional Flow Reserve Measured Immediately After Drug-Eluting Stent Implantation

Abstract: Background— The predictive value of fractional flow reserve (FFR) measured immediately after percutaneous coronary intervention (PCI) with drug-eluting stent placement has not been prospectively investigated. We investigated the potential of post-PCI FFR measurements to predict clinical outcome in patients from FAME 1 and 2 trials (Fractional Flow Reserve or Angiography for Multivessel Evaluation). Methods and Results— All patients of FAM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
104
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 44 publications
6
104
0
1
Order By: Relevance
“…One meta‐analysis showed that post‐PCI FFR < 0.9 is associated with a higher rate of death, MI, and repeated revascularization . The Fractional Flow Reserve Versus Angiography for Multivessel Evaluation (FAME) substudy demonstrated that a higher post‐PCI FFR was related to a better clinical outcome; however, no discrete cutoff value was proposed as a prognostic predictor or as a target value for further optimization of PCI. As such, despite a direct relationship between post‐PCI FFR and clinical outcomes, it is still unclear whether post‐PCI FFR predicts the prognosis in DES‐treated patients or whether it is useful to guide further actions to optimize immediate PCI results and long‐term clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One meta‐analysis showed that post‐PCI FFR < 0.9 is associated with a higher rate of death, MI, and repeated revascularization . The Fractional Flow Reserve Versus Angiography for Multivessel Evaluation (FAME) substudy demonstrated that a higher post‐PCI FFR was related to a better clinical outcome; however, no discrete cutoff value was proposed as a prognostic predictor or as a target value for further optimization of PCI. As such, despite a direct relationship between post‐PCI FFR and clinical outcomes, it is still unclear whether post‐PCI FFR predicts the prognosis in DES‐treated patients or whether it is useful to guide further actions to optimize immediate PCI results and long‐term clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring coronary pressure and determining FFR may optimize implantation of bare‐metal stents . However, the prognostic value of post‐PCI FFR for predicting clinical outcomes after implantation of a drug‐eluting stent (DES) is controversial …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a registry of 750 patients receiving bare metal stents, Pijls et al reported that at 6‐month follow‐up, the lowest event rates occurred in patients with post‐PCI FFR ≥0.90 . Studies and related meta‐analyses involving drug‐eluting stents have suggested similar cutoff values of post‐PCI FFR to predict improved clinical outcomes . These range from 0.89 to ≥0.92 with a large systematic review and meta‐analysis of 7470 patients concluding that a post‐PCI FFR ≥0.90 was associated with a significantly lower risk of repeat PCI and major adverse cardiovascular events .…”
Section: Introductionmentioning
confidence: 99%
“…Published values for overall mean or median final post‐PCI FFR results range from 0.84 to 0.95 . The proportion of patients actually achieving a final FFR ≥0.90 varies widely between studies and ranges from 37% to 93% .…”
Section: Introductionmentioning
confidence: 99%